Adsorptive Removal of Methyl Red from Aqueous Solution using Charred and Xanthated Sal (Shorea robusta) Sawdust - Dawadi, Krishna Bahadur; Bhattarai, Mahesh; Homagai, Puspa Lal (Amrit Research Journal, 2020)
Adsorptive removal of methyl red (MR) from aqueous solution onto chemically modified Charred Sal (Shorea robusta) Saw-Dust (CSSD) and Xanthated Sal Saw-Dust (XSSD) has been investigated. The surface modification is characterized by Fourier transformed infra-red (FTIR) spectroscopy, scanning electron microscopy (SEM) and elemental Analysis. Different parameters are studied such as contact time, optimum pH, and initial ion concentration. Maximum dye removal is observed at pH 4 for charred and xanthated Sal saw dust. The dye can be quantitatively removed onto the surface of these adsorbent. At a contact time of 3-4 hours maximum adsorption capacity (qmax) for CSSD and XSSD are found to be 70 mg/g and 130 mg/g respectively. Adsorption kinetic data are best fitted onto pseudo second order. The obtained result indicated an excellent alternative for the treatment of dye contaminated waste water using such chemically modified Sal saw dust at low cost with better efficiency.